Beirut air pollution and health effects-BAPHE study protocol and objectives - Nakhle, Myrian Mrad (2015)
Background Recent studies investigating the health effects of air pollution have proven an existing impact around and below international air quality guidelines and standards. These studies were based on accessible data from official registers managed by public authorities. The protocol followed in BAPHE project is described; its benefits and disadvantages are presented and discussed in this paper. Methods Based on the review of several international studies we developed a custom made approach in BAPHE (Beirut Air Pollution and Health Effects) project in order to analyze the short term health effects of air pollution taking into consideration the lack of data availability from official sources. Results PM2.5 and PM10 concentrations were measured in Beirut for the period starting from the 1st of January 2012 to the 31st of December 2012. The annual average concentrations of PM10 and PM2.5 exceeded WHO’s annual average limits by 150 % and 200 %, respectively. Health data for 11,567 individuals were collected over 12 months. A variation of hospital admission causes was observed by age categories and gender. Conclusions This article presents a simple protocol and the descriptive results of its application in the frame of an eco-epidemiological study in Lebanon. We believe that this work is not only important on a local scale, but it could be helpful for environmental epidemiological studies in other countries